COVID-19 and serious mental illness: Experience from a psychiatric hospital in Cape Town, South Africa - Sablay, Haseena (Department of Psychiatry and Mental Health, 2025)
Background: Several factors make patients admitted to specialist psychiatric units more vulnerable and susceptible to infections like SARS-COV-2. This includes psychiatric hospital infrastructure and service design, patients' mental health profiles, and staff's medical skills. Aim: To describe the psychiatric and medical profile, and the risk factors associated with more severe disease and clinical outcomes of COVID-19 in patients with severe mental illness (SMI) admitted to a specialist psychiatric hospital in South Africa between 1 April 2020 and 30 September 2021. Setting: Valkenberg Hospital (VBH), a psychiatric hospital in Cape Town. Method: Demographic and clinical information were collected on all VBH in-patients who tested positive for SARS-COV-2 from 1 April 2020 to 30 September 2021. Results: Two hundred and fifty-four participants tested positive for SARS-COV-2. The sample included 75% (n=191) males with a mean age of 35,7 years. Most patients were diagnosed with schizophrenia 37% (n=94), bipolar disorder 21% (n=54) and schizoaffective disorder 19% (n=49). Comorbidities reported were nicotine use 71% (n=181), hypertension 11% (n=28), and HIV 7% (n=18). Most patients, 62% (n=156), were symptomatic for COVID-19. 7% (n=17) required transfer to a medical ward. Almost all patients, 99% (n=252), recovered, and 1% (n=2) died. Conclusion: Despite the concerns that SMI and high substance use rates would worsen outcomes, most patients had mild illnesses and recovered. This contrasts with concerns raised early in the pandemic that institutionalised patients with SMI were at increased risk of mortality and an increased hospitalisation rate for COVID-19. Contribution: This descriptive study provided information on COVID-19 disease at a specialist psychiatric hospital during the pandemic.